1997
DOI: 10.1016/s0304-3959(97)00077-8
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation attenuates augmented dorsal horn release of excitatory amino acids in mononeuropathy via a GABAergic mechanism

Abstract: Neuropathic pain may be effectively relieved by electric stimulation of the spinal cord (SCS). However, the underlying mechanisms for the ensuing pain relief are poorly understood. In a rat model of neuropathy displaying hypersensitivity to innocuous tactile stimuli, (allodynia), we have earlier demonstrated that SCS may normalise withdrawal response thresholds. In the present study, using microdialysis, it is shown that SCS induces a decreased release of the dorsal horn excitatory amino acids (EAA), glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
257
0
10

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(271 citation statements)
references
References 32 publications
4
257
0
10
Order By: Relevance
“…The analgesic action of baclofen and morphine seems to involve, at least in part, common neural substrates located somewhere in the pons and anterior third of the medulla 23. However, the active sites in the brainstem differ from that of morphine 24. On the other hand, Cui et al 25 have recently shown that spinal cord stimulation exerts its analgesic effect by an activation of local GABA-ergic mechanisms, inhibiting excitatory aminoacid release, thus reinforcing the notion of GABA participation in spontaneous and evoked analgesia.…”
Section: Discussionmentioning
confidence: 88%
“…The analgesic action of baclofen and morphine seems to involve, at least in part, common neural substrates located somewhere in the pons and anterior third of the medulla 23. However, the active sites in the brainstem differ from that of morphine 24. On the other hand, Cui et al 25 have recently shown that spinal cord stimulation exerts its analgesic effect by an activation of local GABA-ergic mechanisms, inhibiting excitatory aminoacid release, thus reinforcing the notion of GABA participation in spontaneous and evoked analgesia.…”
Section: Discussionmentioning
confidence: 88%
“…28 It is of special interest that this effect on the GABA system occurred only in rats that in preceding experiments had been found to respond to SCS with significant suppression of hind paw hypersensitivity. 29 These results confirm earlier observations that the state of central hyperexcitability manifested in the development of allodynia after peripheral nerve injury relates to dysfunction of the spinal GABA systems, and it appears that SCS may act by restoring normal GABA levels in the dorsal horn.…”
Section: What Is Known About Transmitter Mechanisms Involved In Scs?mentioning
confidence: 98%
“…The same potentiating effect was found with adenosine and it can thus be concluded that both the GABAand the adenosine-related systems are directly involved in the pain relieving effect of SCS. 28,31 These results initiated a clinical study where it was demonstrated that it was possible to enhance the SCS effect by simultaneous intrathecal administration of baclofen in low doses. 32 Again, this is a good example of direct transfer of results ''from the bench to bedside'' application.…”
Section: What Is Known About Transmitter Mechanisms Involved In Scs?mentioning
confidence: 99%
“…As the afterdischarge in response to innocuous touch stimulation is depressed by an NK-1 receptor antagonist (Pitcher and Henry, 2004), presumably due to blocking the effects of tonic release of substance P (Malcangio et al, 2000), it is tempting to extrapolate from the results of the present study that the gain in excitability of dorsal horn neurons in response to innocuous cutaneous stimulation may also be due to persisting peripheral drive. Thus, persisting hyperalgesia and/or allodynia that occurs following mechanical stimulation in people who suffer neuropathic pain may be due to altered afferent input that is mediated by continuous release of neurotransmitters (Wang et al, 2007) such as glutamate (Cui et al, 1997;Kawamata and Omote, 1996;Somers and Clemente, 2002) and peptide neuromodulators including substance P Ma and Bisby, 1998;Malcangio et al, 2000) and CGRP (Helgren et al, 1999;Lee and Kim, 2007;Ma and Bisby, 1998).…”
Section: Contribution Of Ectopic Afferent Inputs To Exaggerated Respomentioning
confidence: 99%